A missense mutation in melanocortin 1 receptor is associated with the red coat colour in donkeys. (25th August 2014) - Abitbol, M.; Legrand, R.; Tiret, L.
Summary The seven donkey breeds recognised by the French studbook are characterised by few coat colours: black, bay and grey. Normand bay donkeys seldom give birth to red foals, a colour more commonly seen and recognised in American miniature donkeys. Red resembles the equine chestnut colour, previously attributed to a mutation in the melanocortin 1 receptor gene (MC1R). We used a panel of 124 donkeys to identify a recessive missense c.629T>C variant in MC1R that showed a perfect association with the red coat colour. This variant leads to a methionine to threonine substitution at position 210 in the protein. We showed that methionine 210 is highly conserved among vertebrate melanocortin receptors. Previous in silico and in vitro analyses predicted this residue to lie within a functional site. Our in vivo results emphasised the pivotal role played by this residue, the alteration of which yielded a phenotype fully compatible with a loss of function of MC1R. We thus propose to name the c.629T>C allele in donkeys the e allele, which further enlarges the panel of recessive MC1R loss‐of‐function alleles described in animals and humans.